2019
DOI: 10.2217/bmm-2018-0449
|View full text |Cite
|
Sign up to set email alerts
|

Altered Signature of Apoptotic Endothelial Cell-Derived Microvesicles Predicts Chronic Heart Failure Phenotypes

Abstract: Aim: to evaluate the associations between signatures of apoptotic endothelial cell-derived microvesicles (MVs) with phenotypes of chronic heart failure (HF). Methods: The study cohort consisted of 388 prospectively involved subjects with HF patients with predominantly reduced left ventricular ejection fraction (HFrEF), HF with preserved ejection fraction (HFpEF) and HF with mid-range ejection fraction (HFmrEF). All biomarkers were measured at baseline. Results: The number of circulating CD31+/annexin V+ MVs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The 28 selected studies included a wide range of potential novel diagnostic HFpEF circulating biomarkers ( Table 1 ). 22–49 …”
Section: Resultsmentioning
confidence: 99%
“…The 28 selected studies included a wide range of potential novel diagnostic HFpEF circulating biomarkers ( Table 1 ). 22–49 …”
Section: Resultsmentioning
confidence: 99%
“…Initially, our results revealed that mice with I/R presented myocardial fibrosis, significant enhanced cell apoptosis and inflammatory response in myocardial tissues, yet HUVECs-EVs reversed these unfavorable results. Interestingly, apoptotic endothelial cell-derived EVs have been identified to predict chronic heart failure phenotypes and reduce left ventricular ejection fraction of patients with chronic heart failure (Berezin et al, 2016(Berezin et al, , 2019. HUVECs-released exosomes were able to prevent nerve cells against I/R in cerebral ischemia (Xiao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The total number of endothelial cell-derived EVs was significantly and positively correlated with oxidative stress and systemic inflammation in healthy younger individuals. While the ability of activated endothelial cells to release EVs packed with proangiogenic molecules progressively decreases in patients with established CAD, apoptotic endothelial cell-derived EVs appear to be detected in higher concentrations [57,58] . This phenomenon probably reflects maladaptive responses of the endothelium in advanced atherosclerosis and decreased control of local vascular inflammation is associated with an altered, intra-plaque immune phenotype of the cells including macrophages and endothelial cells [ Figure 2].…”
Section: Modification Of Macrophages' Phenotype and Functionmentioning
confidence: 98%